Toll-like receptor signaling pathway triggered by inhibition of serpin A1 stimulates production of inflammatory cytokines by endometrial stromal cells - Kusama, Kazuya; Satoyoshi, Ayaka; Azumi, Mana; Yoshie, Mikihiro; Kojima, Junya; Mizuno, Yumi; Ono, Masanori; Nishi, Hirotaka; Kajihara, Takeshi; Tamura, Kazuhiro (Frontiers in Endocrinology, 2022)
Endometriosis is characterized by the presence of inflamed and fibrotic endometrial tissue outside the uterine cavity. Previously, we found decreased SERPINA1 (alpha-1 antitrypsin) expression in endometriosis-like lesions in a mouse model of endometriosis, suggesting that it exacerbated inflammation in these lesions. However, the molecular mechanism(s) by which SERPINA1 affects expression of inflammatory factors and development of endometriotic lesions have not been fully characterized. To investigate the role of intracellular SERPINA1 in endometrial stromal cells (ESCs), we performed RNA sequence analysis using RNA extracted from ESCs in which SERPINA1 was knocked down. The analysis identified several toll-like receptor (TLR)-related factors as being upregulated. Silencing of SERPINA1 increased expression of TLR3 and TLR4 in ESCs, as well as several TLR signaling pathway components, including MYD88, IRAK1/4, interleukin (IL)-1β, and interferon (IFN)-β. TLR3 or TLR4 agonists increased expression of inflammatory factors in SERPINA1-knockdown ESCs, whereas TLR3 or TLR4 inhibitors decreased expression. In addition, treatment with recombinant IL-1β or IFN-β increased expression of MYD88 and inflammatory factors in ESCs. Immunohistochemical analysis of endometriotic tissues showed that TLR3, TLR4, and MYD88 were localized in endometriosis lesions. Taken together, the data suggest that reduced expression of SERPINA1 induces expression of inflammatory factors by ESCs, which in turn are associated with TLR3/4, IL-1β, and IFN-β signaling. Regulation of intracellular SERPINA1 levels in ESCs may be a strategy to inhibit inflammatory responses in endometriotic lesions.